A Stylistic Analysis of Imperative Mood on Hannah Baker’s Monologue - 13 Reasons Why (Season 1) - Rosa Gita Cahyani; Chusni Hadiati; Nadia Gitya Yulianita (J-Lalite: Journal of English Studies, 2021)
The appearance of a sentence that is continuously uttered by the speaker becomes a style or characteristic of the speaker. This can be seen in a series entitled 13 Reasons Why in which the main character, Hannah Baker, uttered many imperative moods. This research focuses on how the use of one form of sentences, namely imperative or what is called as imperative mood, can give a stylistic effect that appears on the utterances of Hannah Baker in a monologue. This research uses a qualitative method that aims 1) to find out the forms of the imperative mood; and 2) to find out the functions of the form of the imperative mood using the theory of Aikhenvald (2010). By observing and transcribing, the data can be found, which then can be identified to find out the imperative sentence, what form and function of it. Through these things, a conclusion can be drawn about how the character of Hannah Baker's is seen from the imperative mood that she utters and what meaning she wants to convey through the imperative mood. This research uses purposive sampling in collecting the data. Based on the results of the study, 54 imperatives mood were found in the monologue. The findings reveal two forms of imperatives namely canonical imperative as many as 77.78% and non-canonical imperative as many as 22.22%. The functions of imperatives found include: 1. Orders, commands, demands (only commands), 2. Requests, pleas, entreaties, 3. Advice, recommendations, warnings, 4. Instructions and expository directives, 5. Invitations, 6. Permission, 7. Acceptance, 8. Incredulous rejection, and 9. Self-deliberation. From the results obtained, it can be seen that the most dominant function is instruction, which is 16.67%. From this result, it can be known that Hannah Baker wanted to show each incident in detail that caused her suicide through her monologue in 13 Reasons Why (Season 1).